Sodium-ion battery positive electrode material as well as preparation method and application thereof
By using specific molar ratio and layered modification strategies of nickel, manganese, tellurium and calcium in the positive electrode materials of sodium ion battery, the phase change problem of sodium ion battery phase change during charging is solved, and the electrochemical performance and cycle of the battery are improved. stability.
Patent Information
- Application Number
- CN202411469720.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-07
AI Technical Summary
During the charging process, the repulsion force between O2--O2- increases, resulting in a phase transition problem from P2 to O2, resulting in a decrease in the electrical performance of the battery and a safety hazard.
The specific molar ratio of nickel, manganese, and tellurium elements and the synergistic effect of calcium elements is adopted to regulate the microstructure of the precursor through a layered modification strategy, maintain the structural stability of the sodium layer, and inhibit the repulsion between O2--O2-.
It effectively maintains the pure P2 structure of the positive electrode material of sodium ion battery, improves capacity performance and cycling performance, and enhances the overall electrochemical performance and long-term cycle stability of the battery.
Smart Images

Figure CN119390019A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, with the growing demand for lithium resources and the relatively high price of lithium resources, the scientific research community is looking for a more cost-effective alternative energy storage solution. Considering the many similarities between sodium and lithium in physical properties and chemical behavior, sodium-ion batteries are increasingly highlighting their research value and application potential, which is expected to ease the dependence on scarce lithium resources and open up a new energy storage path that is economical, efficient and sustainable.
[0003] Sodium ions have a larger size relative to lithium ions, which affects the diffusion rate and kinetics of sodium ions in layered materials, which may lead to slow kinetic response and higher polarization during charge and discharge, thus affecting the overall performance of the battery. Compared with commercial lithium-ion battery cathode materials, sodium ion cathode materials have lower energy density and shorter cycle life. This limits the competitiveness of sodium-ion batteries in practical applications, especially in scenarios that require high energy density and long cycle stability.
[0004] Among them, layered sodium-ion oxide cathode materials have shown great potential in high-energy-density energy storage applications due to their excellent specific capacity characteristics. The technical development path of these materials is quite mature, and their production processes are highly compatible with the existing manufacturing processes in the lithium-ion battery industry, which means that existing lithium-ion production lines only need to be slightly adjusted to quickly transform into the production of sodium-ion batteries, greatly promoting the industrialization of sodium-ion batteries. In addition, the large-scale production of layered sodium-ion oxide materials not only benefits from a mature process foundation, but also makes full use of existing equipment in the lithium-ion industry, ensuring efficient and economical capacity expansion, paving the way for the commercial application of sodium-ion batteries. However, during the charging process, the layered sodium-ion oxide cathode materials are 2- -O 2- As the repulsive force between them increases, a phase transition from P2 to O2 will occur, which leads to a significant attenuation of battery performance and an increase in battery safety risks. 2- The high activity may cause side reactions with the electrolyte to produce gas, which may cause thermal runaway and potential explosion risks.
[0005] This problem stems from the effect of sodium ions on the oxygen layer during the deintercalation process, especially when the sodium ion concentration decreases. 2- -O 2-The distance between the electrodes is reduced, resulting in a stronger repulsive force, which destroys the structural stability of the material. Due to phase change and structural instability, layered sodium ion oxide cathode materials will experience capacity decay after long-term cycling, which is one of the main obstacles to the commercial application of sodium ion batteries. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the problem that during the use of the prior art sodium ion battery, due to the 2- -O 2- The repulsive force between them increases, resulting in a phase change problem from P2 to O2, which leads to a decrease in the electrical performance of the battery and a potential safety hazard. Thus, a sodium ion battery positive electrode material and a preparation method and application thereof are provided.
[0007] To this end, the present invention provides the following technical solutions:
[0008] The first aspect of the present invention protects a method for preparing the aforementioned sodium ion battery positive electrode material, wherein the preparation method comprises the following steps:
[0009] S1, a nickel source, a manganese source, a tellurium source and water are first mixed to obtain a mixed solution, a precipitant and a chelating agent are added to react, aged, and first dried to obtain a precursor;
[0010] S2, performing a second mixing of the precursor, the sodium source, and the calcium source, performing a second drying and compacting, and performing sintering to obtain a positive electrode material for a sodium ion battery.
[0011] In the present invention, a washing step is further included after aging.
[0012] According to the present invention, the tellurium source includes tellurium-containing oxide and / or telluric acid.
[0013] According to the present invention, the tellurium source includes any one of TeO2, H2TeO3 and H6TeO6, and H6TeO6 can be selected.
[0014] In the present invention, the nickel source and manganese source are conventional nickel sources and manganese sources in the art. Typically, but not limiting, the nickel source is a soluble nickel salt, including NiSO4·6H2O and / or NiSO4, and the manganese source is a soluble manganese salt, including MnSO4·H2O and / or MnSO4.
[0015] According to the present invention, the molar ratio of the nickel element in the nickel source, the manganese element in the manganese source, and the tellurium element in the tellurium source is (0.9-1):(0.01-0.1):(0.005-0.05).
[0016] According to the present invention, the concentration of the solute in the mixed solution is 1-3 mol / L; the solute refers to the sum of all solutes in the solution, including nickel source, manganese source and tellurium source.
[0017] In the present invention, the precipitant and the chelating agent are both added with water to prepare a solution and then mixed with the mixed solution, so that the reaction mixing is more sufficient; the precipitant is a conventional precipitant in the art, including at least one of NaOH and KOH, and the concentration of the precipitant is 3-5 mol / L; the chelating agent includes at least one of ammonia water and ethylenediaminetetraacetic acid (EDTA), and the concentration of the chelating agent is 0.5-2 mol / L; the volume ratio of the mixed solution, the precipitant solution, and the chelating agent solution is (500-800):(500-800):(100-300).
[0018] According to the present invention, the reaction pH is 11-12, the temperature is 30-60°C, the time is 24-42h, and the stirring speed is 800-1000rpm. In the present invention, the pH refers to the entire system including the mixed solution, the precipitant solution, and the chelating agent solution.
[0019] In the present invention, the aging and the first drying are both conventional methods in the art, wherein the aging time is 10-15 hours; the temperature of the first drying is 100-120° C., and the time is 12-18 hours.
[0020] According to the present invention, the molar ratio of the metal element in the precursor, the sodium element in the sodium source, and the calcium element in the calcium source is 1:(1.1-2):(0.01-0.1).
[0021] In the present invention, the metal elements in the precursor refer to nickel, manganese and tellurium.
[0022] According to the present invention, the sodium source is a soluble sodium salt, including at least one of Na2CO3, NaHCO3, and NaCl.
[0023] According to the present invention, the calcium source is a soluble calcium salt, including at least one of Ca(NO3)2, CaCl2, and Ca(CH3COO)2.
[0024] According to the present invention, the second mixing method is at least one of ball milling and stirring, and stirring can be selected.
[0025] According to the present invention, the rotation speed of the ball mill is 200-500 rpm, and the time is 12-18 hours.
[0026] In the present invention, the second drying temperature is 100-150° C., and the drying time is 1-2 hours.
[0027] According to the present invention, the compacting method is cold pressing.
[0028] According to the present invention, the cold pressing pressure is 8-50 MPa, the temperature is 20-50° C., and the time is 5-10 min.
[0029] According to the present invention, the heating rate of the sintering is 1-5°C / min, the sintering temperature is 700-1200°C, and the sintering time is 8-20h.
[0030] The second aspect of the present invention protects a sodium ion battery positive electrode material prepared by the above-mentioned preparation method, wherein the chemical formula of the sodium ion battery positive electrode material is Na i Ni x Mn y Te a Ca b O2, where 1.2≤i≤2, 0.9≤x≤1, 0.01≤y≤0.1, 0.005≤a≤0.05, 0.01≤b≤0.1, x+y+a=1.
[0031] A third aspect of the present invention protects a secondary battery, wherein the secondary battery comprises the sodium ion battery positive electrode material obtained by the aforementioned preparation method or the aforementioned sodium ion battery positive electrode material.
[0032] In the present invention, the positive electrode material of the sodium ion battery is prepared into a battery. The specific method is: the positive electrode material, polyvinylidene fluoride and carbon black are mixed in a ratio of 95:2.5:2.5 and then coated to form a battery with a compaction density of 3-4g / cm 3 The electrode is made of a metal sodium sheet as the counter electrode, a glass fiber as the separator, and an electrolyte of 1-1.1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC), with a volume ratio of EC to DMC of 1:1. The entire assembly process was carried out in an argon-filled glove box to produce a CR2032 button cell.
[0033] The technical solution of the present invention has the following advantages:
[0034] 1. The present invention provides a method for preparing a positive electrode material for a sodium ion battery, wherein the preparation method comprises the following steps: S1, first mixing a nickel source, a manganese source, a tellurium source and water to obtain a mixed solution, adding a precipitant and a chelating agent to react, aging, and first drying to obtain a precursor; S2, second mixing the precursor, a sodium source and a calcium source, compacting after the second drying, and sintering to obtain a positive electrode material for a sodium ion battery; the present invention adopts a layered modification strategy, firstly introducing tellurium elements to regulate the particle morphology of the precursor microstructure to better adapt to the lattice strain, and realizing the Te-Ni-Ni-Te ordered superstructure in the layer, effectively regulating the ligand energy level structure and inhibiting the lattice oxygen loss; then adding calcium elements to anchor the sodium site to maintain the cation content in the sodium layer, and the tellurium elements and calcium elements act synergistically to alleviate the O2- -O 2- Repulsion enables the prepared sodium ion battery cathode material to maintain a pure P2 type structure, thus having excellent capacity performance and cycle performance;
[0035] In addition, in the present invention, the nickel source, manganese source and tellurium source are first added and mixed, and then the precipitant and the chelating agent are added, so that the reaction is more controllable, and the particle morphology and uniformity of the prepared positive electrode material are also significantly improved.
[0036] 2. H6TeO6 of the present invention as high-valent Te 6+ Doping can further improve the uniformity of the reaction, form a uniform precipitation, and improve the electrochemical properties of the material, especially the cycle performance of the battery.
[0037] 3. The specific molar ratio of the nickel element in the nickel source, the manganese element in the manganese source, and the tellurium element in the tellurium source of the present invention can further improve the capacity retention rate of the material during the cycle, thereby improving the overall electrochemical performance and long-term cycle of the sodium ion battery positive electrode material.
[0038] 4. The specific molar ratio of the metal element in the precursor of the present invention, the sodium element in the sodium source, and the calcium element in the calcium source can further improve the ion migration rate and the stability of the crystal structure of the electrode material during the charge and discharge process, thereby improving the cycle life and electrical performance of the battery.
[0039] 5. The second mixing method of the present invention adopts ball milling, which further improves the uniformity and activity of the material. Through the mechanical force of ball milling, the components are fully mixed and can be refined, and the contact area between fine particles is increased, which helps to alleviate the local stress concentration phenomenon. At the same time, good uniformity also allows the material to form a more uniform microstructure after cold pressing, thereby reducing potential stress concentration areas and making metal elements and other materials evenly distributed at the molecular or nanometer level; this uniformity helps to improve the reaction activity of the material, optimize the structural stability and conductivity of the positive electrode material of the sodium ion battery, thereby improving the electrochemical performance and cycle stability of the battery.
[0040] 6. The cold pressing method adopted in the present invention can further bring higher density and good inter-particle bonding force. By applying uniform pressure during the cold pressing process, the mechanical strength and stability of the material are further improved, thereby reducing cracks and defects during the sintering process. The present invention selects appropriate pressure and time during the cold pressing process. These process parameters are optimized to effectively reduce stress concentration caused by excessive compression force. At the same time, by sintering after cold pressing, the internal stress that may be generated during the cold pressing stage can be further alleviated. This optimized structure helps to improve the conductivity and ion migration rate of battery materials, further improve the overall electrochemical performance of sodium ion batteries, and enhance their cycle performance.
[0041] 7. The specific sintering conditions of the present invention can further improve the phase purity and uniformity of the microstructure of the material. By precisely controlling the sintering temperature, heating rate and holding time, better mutual diffusion and crystal reconstruction are achieved, thereby promoting the growth and optimization of grains inside the material. Such an optimized microstructure effectively reduces the interface impedance, improves the ionic conductivity, and further improves the electrochemical performance of the positive electrode material of the sodium ion battery, including higher capacity and excellent cycle stability.
[0042] 8. The present invention provides a sodium ion battery positive electrode material, wherein the chemical formula of the sodium ion battery positive electrode material is Na i Ni x Mn y Te a Ca b O2, wherein 1.2≤i≤2, 0.9≤x≤1, 0.01≤y≤0.1, 0.005≤a≤0.05, 0.01≤b≤0.1, x+y+a=1; tellurium and calcium are introduced into the sodium ion battery of the present invention to stabilize the charge distribution between the positive electrode material layers, maintain the spacing between the sodium layers, and inhibit O 2- -O 2- The repulsive force between 2- stability, thereby improving the electrochemical performance and cycle stability of sodium ion batteries containing sodium ion battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 XRD pattern of the sodium ion battery positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0045] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0046] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0047] Example 1
[0048] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0049] S1, mixing NiSO4·6H2O, MnSO4·H2O and H6TeO6 in a molar ratio of 0.94:0.05:0.01 with ionized water to prepare 500 mL of a mixed solution with a solute concentration of 2 mol / L, adding 500 mL of a 4 mol / L NaOH solution as a precipitant, adding 100 mL of 1 mol / L ammonia water as a chelating agent to react, the pH of the reaction is maintained at 11, the reaction temperature is 55° C., the reaction time is 30 h, and the stirring speed is 900 rpm; aging for 10 h, then washing the precursor with deionized water for multiple times to remove impurities, and drying in an oven at 110° C. for 12 h to obtain a precursor;
[0050] S2, put the precursor, Na2CO3, and Ca(NO3)2 into a ball mill and mix them, wherein the molar ratio of the sum of nickel, manganese and tellurium in the precursor, sodium in Na2CO3, and calcium in Ca(NO3)2 is 1:1.22:0.05, and mix them evenly at a speed of 300rpm for 12h, then dry the mixed raw materials at 120℃ for 1h, and then cold press them at a pressure of 10MPa and a temperature of 25℃ for 5min to obtain compacted particles. In an air atmosphere, the particles are sintered at 900℃ for 15h at a heating rate of 2℃ / min. After natural cooling, the materials are crushed and sieved to form fine powders to obtain sodium ion battery positive electrode materials;
[0051] XRD patterns of positive electrode materials for sodium ion batteries Figure 1 As shown, from Figure 1 It can be seen that our material is a standard P2 phase and no other impurities are introduced.
[0052] Example 2
[0053] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0054] S1, MnSO4·H2O, NiSO4·6H2O and H6TeO6 in a molar ratio of 0.98:0.01:0.01 were mixed with ionized water to prepare 600 mL of a mixed solution with a solute concentration of 3 mol / L, 600 mL of a 3 mol / L NaOH solution was added as a precipitant, and 200 mL of a 2 mol / L ammonia solution was added as a chelating agent for reaction, the pH of the reaction was maintained at 12, the reaction temperature was 30° C., the reaction time was 40 h, and the stirring speed was 1000 rpm; aging for 15 h, then washing the precursor with deionized water for several times to remove impurities, and drying in an oven at 120° C. for 15 h to obtain a precursor;
[0055] S2, put the precursor, Na2CO3, and Ca(NO3)2 into a ball mill and mix them. The molar ratio of the sum of nickel, manganese and tellurium in the precursor, sodium in Na2CO3, and calcium in Ca(NO3)2 is 1:1.24:0.04. Mix them evenly at a speed of 500rpm for 15h, then dry the mixed raw materials at 150℃ for 2h, and then cold press them for 10min at a pressure of 15MPa and a temperature of 30℃ to obtain compacted particles. In an air atmosphere, sinter the particles at 1000℃ for 20h at a heating rate of 5℃ / min. After natural cooling, crush and sieve the materials to make fine powder to obtain the positive electrode material of sodium ion battery.
[0056] Example 3
[0057] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0058] The method of Example 1 is the same, except that H6TeO6 is replaced by an equimolar amount of TeO2 in step S1.
[0059] Example 4
[0060] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0061] The method of Example 1 is the same, except that H6TeO6 is replaced by an equimolar amount of H2TeO3 in step S1.
[0062] Example 5
[0063] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0064] The method of Example 1 is followed, except that NiSO4.6H2O, MnSO4.H2O and H6TeO6 in a molar ratio of 0.94:0.04:0.02 are mixed with ionized water.
[0065] Example 6
[0066] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0067] The method of Example 1 is the same, except that the precursor, Na2CO3, and Ca(NO3)2 are placed in a ball mill and mixed, wherein the molar ratio of the sum of nickel, manganese and tellurium elements in the precursor, sodium in Na2CO3, and calcium in Ca(NO3)2 is 1:1.18:0.07.
[0068] Example 7
[0069] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0070] The method of Example 1 is the same, except that in S2, the precursor, Na2CO3, and Ca(NO3)2 are stirred at a uniform speed, wherein the molar ratio of the sum of nickel, manganese and tellurium in the precursor, sodium in Na2CO3, and calcium in Ca(NO3)2 is 1:1.22:0.05, the stirring speed is 300 rpm, and the time is 12 h.
[0071] Example 8
[0072] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0073] The method of Example 1 is the same, except that the cold pressing pressure is 50 MPa.
[0074] Example 9
[0075] This embodiment provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0076] The method of Example 1 is the same, except that the sintering conditions are: sintering at 700° C. for 8 h at a heating rate of 5° C. / min.
[0077] Comparative Example 1
[0078] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0079] S1, mixing NiSO4·6H2O and MnSO4·H2O with a molar ratio of 0.94:0.06 with ionized water to prepare 500 mL of a mixed solution with a solute concentration of 2 mol / L, adding 500 mL of a 4 mol / L NaOH solution as a precipitant, adding 100 mL of 1 mol / L ammonia water as a chelating agent for reaction, maintaining the pH of the reaction at 11, the reaction temperature at 55° C., the reaction time at 30 h, and the stirring speed at 900 rpm; aging for 10 h, then washing the precursor with deionized water for multiple times to remove impurities, and drying in an oven at 110° C. for 12 h to obtain a precursor;
[0080] S2, put the precursor, Na2CO3, and Ca(NO3)2 into a ball mill and mix them, wherein the molar ratio of the sum of nickel and manganese elements in the precursor, sodium in Na2CO3, and calcium in Ca(NO3)2 is 1:1.22:0.05, and mix them evenly at a speed of 300rpm for 12h, then dry the mixed raw materials at 120℃ for 1h, and then cold press them at a pressure of 10MPa and a temperature of 25℃ for 5min to obtain compacted particles. In an air atmosphere, the particles are sintered at 900℃ for 15h at a heating rate of 2℃ / min. After natural cooling, the materials are crushed and sieved to form fine powders to obtain the positive electrode materials for sodium ion batteries.
[0081] Comparative Example 2
[0082] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0083] S1, NiSO4·6H2O and MnSO4·H2O in a molar ratio of 0.94:0.06 were mixed with ionized water to prepare 500 mL of a mixed solution with a solute concentration of 2 mol / L, 500 mL of a 4 mol / L NaOH solution was added as a precipitant, and 100 mL of 1 mol / L ammonia water was added as a chelating agent for reaction, the pH of the reaction was maintained at 11, the reaction temperature was 55° C., the reaction time was 30 h, and the stirring speed was 900 rpm; aged for 10 h, then the precursor was washed with deionized water for several times to remove impurities, and dried in an oven at 110° C. for 12 h to obtain a precursor;
[0084] S2, put the precursor and Na2CO3 into a ball mill and mix them, wherein the molar ratio of the sum of nickel and manganese elements in the precursor and the sodium element in Na2CO3 is 1:1.22, and mix them evenly at a speed of 300rpm for 12h, then dry the mixed raw materials at 120℃ for 1h, and then cold press them at a pressure of 10MPa and a temperature of 25℃ for 5min to obtain compacted particles. In an air atmosphere, the particles are sintered at 900℃ for 15h at a heating rate of 2℃ / min. After natural cooling, the materials are crushed and sieved to form fine powders to obtain the positive electrode materials for sodium ion batteries.
[0085] Comparative Example 3
[0086] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0087] S1, according to the method of Example 1;
[0088] S2, put the precursor and Na2CO3 into a ball mill and mix them, wherein the molar ratio of the sum of nickel, manganese and tellurium in the precursor and the sodium in Na2CO3 is 1:1.22, and mix them evenly at a speed of 300rpm for 12h, then dry the mixed raw materials at 120℃ for 1h, and then cold press them at a pressure of 10MPa and a temperature of 25℃ for 5min to obtain compacted particles. In an air atmosphere, the particles are sintered at 900℃ for 15h at a heating rate of 2℃ / min. After natural cooling, the materials are crushed and sieved to form fine powders to obtain the positive electrode materials for sodium ion batteries.
[0089] Comparative Example 4
[0090] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0091] S1, mixing NiSO4·6H2O and MnSO4·H2O with a molar ratio of 0.94:0.05 with ionized water to prepare 500 mL of a mixed solution with a solute concentration of 2 mol / L, adding 500 mL of a 4 mol / L NaOH solution as a precipitant, adding 100 mL of 1 mol / L ammonia water as a chelating agent for reaction, maintaining the pH of the reaction at 11, the reaction temperature at 55° C., the reaction time at 30 h, and the stirring speed at 900 rpm; aging for 10 h, then washing the precursor with deionized water for multiple times to remove impurities, and drying in an oven at 110° C. for 12 h to obtain a precursor;
[0092] S2, put the precursor, Na2CO3, Ca(NO3)2, and H6TeO6 into a ball mill for mixing, wherein the molar ratio of the sum of nickel and manganese elements in the precursor, sodium element in Na2CO3, calcium element in Ca(NO3)2, and tellurium element in H6TeO6 is 1:1.22:0.05:0.01, and mix them evenly at a speed of 300rpm for 12h, and then dry the mixed raw materials at 120℃ for 1h, and then cold press them at a pressure of 10MPa and a temperature of 25℃ for 5min to obtain compacted particles. In an air atmosphere, the particles are sintered at 900℃ for 15h at a heating rate of 2℃ / min. After natural cooling, the materials are crushed and sieved to make fine powder to obtain the positive electrode material of sodium ion battery.
[0093] Comparative Example 5
[0094] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0095] S1, mixing NiSO4·6H2O, MnSO4·H2O, H6TeO6 and Na2CO3 in a molar ratio of 0.94:0.05:0.01:0.61 with ionized water to prepare 500 mL of a mixed solution with a solute concentration of 2 mol / L, adding 500 mL of a 4 mol / L NaOH solution as a precipitant, adding 100 mL of 1 mol / L ammonia water as a chelating agent to react, the pH of the reaction is maintained at 11, the reaction temperature is 55° C., the reaction time is 30 h, and the stirring speed is 900 rpm; aging for 10 h, then washing the precursor with deionized water for several times to remove impurities, and drying in an oven at 110° C. for 12 h to obtain a precursor;
[0096] S2, put the precursor and Ca(NO3)2 into a ball mill for mixing, wherein the molar ratio of the sum of nickel, manganese and tellurium in the precursor and calcium in Ca(NO3)2 is 1:0.05, and mix them evenly at a speed of 300rpm for 12h, then dry the mixed raw materials at 120℃ for 1h, and then cold press them at a pressure of 10MPa and a temperature of 25℃ for 5min to obtain compacted particles. In an air atmosphere, the particles are sintered at 900℃ for 15h at a heating rate of 2℃ / min. After natural cooling, the materials are crushed and sieved to form fine powders to obtain the positive electrode materials for sodium ion batteries.
[0097] Comparative Example 6
[0098] This comparative example provides a method for preparing a positive electrode material for a sodium ion battery, which is as follows:
[0099] In accordance with the method of Example 1, the difference is that, S2, the precursor, Na2CO3, and Ca(NO3)2 are put into a ball mill for mixing, wherein the molar ratio of the sum of nickel element, manganese element and tellurium element in the precursor, sodium element in Na2CO3, and calcium element in Ca(NO3)2 is 1:1.22:0.05, and the mixture is evenly mixed at a rotation speed of 300 rpm for 12 hours, and then the mixed raw materials are dried at 120°C for 1 hour, and the particles are sintered at 900°C for 15 hours at a heating rate of 2°C / min in an air atmosphere. After natural cooling, the material is crushed and sieved to form a fine powder to obtain a sodium ion battery positive electrode material.
[0100] Test Case
[0101] The positive electrode material of the sodium ion battery is prepared into a battery. The specific method is: the positive electrode material, polyvinylidene fluoride and carbon black are mixed in a ratio of 95:2.5:2.5 and then coated to form a battery with a compaction density of 3.2g / cm 3 The electrode is made of a metal sodium sheet as the counter electrode, a glass fiber as the separator, and an electrolyte of 1 mol / L lithium hexafluorophosphate mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC), with a volume ratio of EC to DMC of 1:1. The entire assembly process was carried out in an argon-filled glove box to produce a CR2032 button cell.
[0102] The battery was placed in a blue battery test system for electrical performance evaluation.
[0103] The charge and discharge specific capacity test is carried out at room temperature. The charge and discharge cut-off voltage is in the range of 2.0-4.0V. First, it is charged to 4.0V at a charge rate of 0.1C, and then discharged to 2.0V at a discharge rate of 0.1C. The first discharge specific capacity at 0.1C is calculated. The calculation formula is: first discharge specific capacity = 0.1C first cycle discharge capacity / mass × 100%.
[0104] Charge to 4.0V at a charge rate of 1C, and then discharge to 2.0V at a discharge rate of 1C. The number of cycles is 50. Calculate the capacity retention rate after 50 cycles. The calculation formula is: 50-cycle capacity retention rate = (50th cycle discharge capacity / 1st cycle discharge capacity) × 100%.
[0105] The specific results are shown in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] Comparison of Example 1, Comparative Example 1 and Comparative Example 3 shows that the Ca element can maintain the cation content of the sodium layer, reducing the O2- -O 2- repulsion and changes in crystal volume, resulting in a significant improvement in cycle stability.
[0110] Comparing Example 1, Example 3, and Example 4, it can be seen that compared with other tellurium sources, H6TeO6 as a high-valent Te 6+ Doping can react evenly with other metal ions to form a uniform precipitation with better performance.
[0111] By comparing Example 1 with Comparative Example 4, it can be seen that although tellurium is added in Comparative Example 4, the performance is still poor. The specific addition sequence of the present invention is conducive to the formation of the required phase of the tellurium source during the solid phase sintering process, thereby obtaining excellent electrical properties.
[0112] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a positive electrode material for a sodium ion battery, characterized in that: The preparation method comprises the following steps: S1, a nickel source, a manganese source, a tellurium source and water are first mixed to obtain a mixed solution, a precipitant and a chelating agent are added to react, aged, and first dried to obtain a precursor; S2, performing a second mixing of the precursor, the sodium source, and the calcium source, performing a second drying and compacting, and performing sintering to obtain a positive electrode material for a sodium ion battery.
2. The preparation method according to claim 1, characterized in that: The tellurium source includes tellurium-containing oxide and / or telluric acid; Optionally, the tellurium source includes any one of TeO2, H2TeO3 and H6TeO6, and H6TeO6 can be selected.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the nickel element in the nickel source, the manganese element in the manganese source, and the tellurium element in the tellurium source is (0.9-1):(0.01-0.1):(0.005-0.05); and / or, the concentration of the solute in the mixed solution is 1-3 mol / L; And / or, the precipitant and the chelating agent are both added with water to form a solution; and / or, the concentration of the precipitant is 3-5 mol / L, and the concentration of the chelating agent is 0.5-2 mol / L; And / or, the volume ratio of the mixed solution, the precipitant solution and the chelating agent solution is (500-800):(500-800):(100-300).
4. The preparation method according to any one of claims 1 to 3, characterized in that The reaction has a pH of 11-12, a temperature of 30-60° C., a reaction time of 24-42 hours, and a stirring speed of 800-1000 rpm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The molar ratio of the metal element in the precursor, the sodium element in the sodium source, and the calcium element in the calcium source is 1:(1.1-2):(0.01-0.1).
6. The preparation method according to any one of claims 1 to 5, characterized in that: The sodium source is a soluble sodium salt, including at least one of Na2CO3, NaHCO3, and NaCl; And / or, the calcium source is a soluble calcium source, including at least one of Ca(NO3)2, CaCl2, and Ca(CH3COO)2.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The compaction method is cold pressing; Optionally, the cold pressing pressure is 8-50 MPa, the temperature is 20-50° C., and the time is 5-10 min; and / or, the second mixing method is at least one of ball milling and stirring, and stirring may be selected; Optionally, the ball milling speed is 200-500 rpm and the time is 12-18 hours.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The heating rate of the sintering is 1-5°C / min, the sintering temperature is 700-1200°C, and the sintering time is 8-20h.
9. A sodium ion battery positive electrode material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The chemical formula of the sodium ion battery positive electrode material is Na i Ni x Mn y Te a Ca b O2, where 1.2≤i≤2, 0.9≤x≤1, 0.01≤y≤0.1, 0.005≤a≤0.05, 0.01≤b≤0.1, x+y+a=1.
10. A secondary battery, characterized in that: The secondary battery comprises the sodium ion battery positive electrode material obtained by the preparation method according to any one of claims 1 to 8 or the sodium ion battery positive electrode material according to claim 9.